2013
DOI: 10.1186/1471-2202-14-70
|View full text |Cite
|
Sign up to set email alerts
|

P-Rex2, a Rac-guanine nucleotide exchange factor, is expressed selectively in ribbon synaptic terminals of the mouse retina

Abstract: BackgroundPhosphatidylinositol (3,4,5)-trisphosphate-dependent Rac Exchanger 2 (P-Rex2) is a guanine nucleotide exchange factor (GEF) that specifically activates Rac GTPases, important regulators of actin cytoskeleton remodeling. P-Rex2 is known to modulate cerebellar Purkinje cell architecture and function, but P-Rex2 expression and function elsewhere in the central nervous system is unclear. To better understand potential roles for P-Rex2 in neuronal cytoskeletal remodeling and function, we performed widefie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 62 publications
(112 reference statements)
0
3
0
Order By: Relevance
“…5 ). Finally, a recent report suggested that P-Rex2 may also be expressed in mouse retinal neurons, 69 but this requires confirmation through knockdown or P-Rex2 −/− controls. For a detailed recent review on the role P-Rex1 and P-Rex2 in neuronal synaptic plasticity and behavior, see reference number.…”
Section: Physiological Functionmentioning
confidence: 99%
“…5 ). Finally, a recent report suggested that P-Rex2 may also be expressed in mouse retinal neurons, 69 but this requires confirmation through knockdown or P-Rex2 −/− controls. For a detailed recent review on the role P-Rex1 and P-Rex2 in neuronal synaptic plasticity and behavior, see reference number.…”
Section: Physiological Functionmentioning
confidence: 99%
“… 33 P-Rex2, GEF that specifically activates Rac small GTPases, is expressed by neurons in the peripheral and central nervous systems. 25 The present study was applied to determine the role of P-Rex2 in the development of the BCP. Our data have showed that P-Rex2 was upregulated in the spinal dorsal horn of the BCP mice.…”
Section: Discussionmentioning
confidence: 99%
“… 24 P-Rex2 is required for spine and synapse development and it has been shown that a decrease in P-Rex2 expression results in reduced spine density. 25 However, the overall link among P-Rex2 and AMPAR in BCP has not been reported.…”
Section: Introductionmentioning
confidence: 99%